2022
DOI: 10.1111/codi.16231
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic transanal drainage tube placement for preventing anastomotic leakage after anterior resection for rectal cancer: A meta‐analysis

Abstract: Aim:The aim was to evaluate the efficacy of transanal drainage tube (TDT) placement for preventing anastomotic leakage after low anterior resection for rectal cancer. Method: PubMed, the Cochrane Central Register of Controlled Trials, Embase and Clini calTr ials.gov databases were searched up to October 2021. Studies comparing outcomes following low anterior resection with or without TDT were included. The primary outcomes measured were anastomotic leakage rate, reoperation rate and anastomotic bleed rate.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The benefit of percutaneous and transanal drainages in elective colorectal surgery regarding AL is controversial. 33–38 In our collective, prophylactic RS drainage did not reduce RSL. In fact, irrigation-suction and transanal drains were associated with increased RSL rates; however, it is for now unclear whether they causally contribute to RSL (ie, via mechanical irritation, foreign body reaction, or transdermal infection) or whether they are intentionally and more frequently placed in high-risk constellations.…”
Section: Discussionmentioning
confidence: 60%
“…The benefit of percutaneous and transanal drainages in elective colorectal surgery regarding AL is controversial. 33–38 In our collective, prophylactic RS drainage did not reduce RSL. In fact, irrigation-suction and transanal drains were associated with increased RSL rates; however, it is for now unclear whether they causally contribute to RSL (ie, via mechanical irritation, foreign body reaction, or transdermal infection) or whether they are intentionally and more frequently placed in high-risk constellations.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies and meta-analyses have found similar results to our study. Guo et al [14] conducted a meta-analysis using the data from three randomized controlled trials (RCTs) and 16 observational studies (prospective or retrospective), nding that use of a TaDT correlated with a reduction in AL in observational studies. A systematic review and meta-analysis conducted by Wang et al indicated that placement of a TaDT decreased the rates of both clinical AL and reoperation related to AL [26].…”
Section: Discussionmentioning
confidence: 99%
“…observational cohort studies concluded that TaDT might represent an e cient and economic intervention for preventing AL after RC surgery [8]. Conversely, Guo et al [14] suggested that using a TaDT in patients with RC did not correlate with any detectable differences in AL according to RCTs. Summarizing the current literature, results were as heterogeneous as they were different in study designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] On the other hand, several publications have also reported conflicting results on associations between TaDT and AL. [15][16][17] Owing to the inherent limitations of the retrospective methodology, relatively small sample size, and nonconcurrent controls, the level of evidence for the application of TaDTs was low, and there were subsequent concerns regarding patient selection bias in these studies. Currently, only a few studies have compared the use of a TaDT to a without TaDT in terms of the rate of AL and perioperative outcomes in patients without a DS.…”
mentioning
confidence: 99%